Assessment and forecast for the creation of photo-chemical smog over transport overpasses in Kyiv - Sipakov, R.; Trofimovich, V.; Voloshkina, O.; Bereznitska, J. (My University, 2018)
This article deals with the analysis of existing of smog situation formation over automobile overpasses and in places of substantial congestion of transport in large cities, for example, in Kyiv. A mathematical model consisting of two blocks – dynamic and kinetic, which allows determining the formation of the thermal dome of pollution and the concentration of hydrocarbon emissions in the air, depending on the number of working engines, is proposed. The kinetic block of the model allows determining the level of formaldehyde, as an indicator of the appearance of photochemical smog in conditions of atmospheric constancy. The concentration of emissions from motor vehicles in the air is calculated over the main transport overpasses of the city of Kyiv at their full load (peak hours).
Keywords: bridge; smog; formaldehyde; indicator of pollution; formation of a dome of pollution; concentration of pollution; hydrocarbons; rate of conversion; mathematical model of atmospheric pollution; 504.056:656.13(477.411)